2018
DOI: 10.1007/s15010-018-1149-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of pulmonary mucormycosis and predictive risk factors for the outcome

Abstract: Pulmonary mucormycosis is a rare infection with a high mortality. Invasive approach for histopathology and culture are crucial for a definite diagnosis. Acute onset patients had a poorer prognosis, and early treatment with antifungal therapy is imperative. Surgical approach is recommended in appropriate patients for a better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
37
2
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 83 publications
9
37
2
1
Order By: Relevance
“…If operated on early, less lung tissue would require resection (ie, an early wedge resection could preempt a later lobectomy). Multilobar involvement was seen more frequently in the study by Lin et al and in numbers similar to ours in the study by Feng and Sun . Our study noted upper lobe predilection, favouring the RUL over the LUL, replicating what has been seen in other studies .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…If operated on early, less lung tissue would require resection (ie, an early wedge resection could preempt a later lobectomy). Multilobar involvement was seen more frequently in the study by Lin et al and in numbers similar to ours in the study by Feng and Sun . Our study noted upper lobe predilection, favouring the RUL over the LUL, replicating what has been seen in other studies .…”
Section: Discussionsupporting
confidence: 91%
“…The clinical presentation of PM is non‐specific and cannot be reliably used in isolation to diagnose PM or distinguish it from other IFIs. Akin to published studies, fever and cough were the most frequently reported symptoms in our study . The relative lesser frequency of hemoptysis, pleuritic chest pain and dyspnoea/hypoxia is also comparable to what has been described in the literature but should still raise suspicion for IFI when present …”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Pulmonary type is the second most common site of involvement and often seen in patients with haematological disorders and transplant recipients [4,5]. Haematological malignancy was the major risk factor (32–40%), followed by diabetes mellitus (32–56%), haematopoietic stem cell transplant (1–9.8%) and solid organ transplant (6.5–9%) and renal disease (13–18%) in pulmonary mucormycosis [129,130,131]. Prakash et al reported post-pulmonary tuberculosis (21%) as one of the risk factors for pulmonary mucormycosis [5].…”
Section: Clinical Forms Of Mucormycosismentioning
confidence: 99%